PERADABAN MASYARAKAT BERBER DI AFRIKA UTARA DAN SPANYOL ABAD 11 M DAN 13 M (STUDI DINASTI MUWAHHIDDUN 524 -667 H/ 1130 â1269 M) - Ohira, Norman (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
This paper examines the Berber civilization / Bedouin in the region of North Africa and Spain (Andalusia) in the 11th and 12th centuries. The study of this quite interesting and unique, especially pay attention to the social conditions of the people who had previously been in the desert region and then move into settled communities / cities (from desert people to sedentary people). Unlike other Islamic regions, the Berber tribes that originally scattered united in a religious movement that subsequently form an Islamic government, one is the Almohads Dynasty (West, al-Mohad). In the beginning Almohads missionary movement led by Ibn Tumart, but later turned into a political movement until the founding of the dynasty by Abdul Mukmin Almohads. Important progress lies in the distinctive architectural style. This Dynasty finally surrender into the hands of the dynasty that won Marriniyyah Marrakech year 1269 AD.Â Tulisan ini mengkaji tentang peradaban masyarakat Berber/ Badui di wilayah Afrika Utara dan Spanyol (Andalusia) pada abad 11 dan 12. Kajian tentang hal ini cukup menarik dan unik terutama ketika memperhatikan kondisi sosial masyarakatnya yang sebelumnya berada pada wilayah padang pasir kemudian berpindah menjadi masyarakat menetap/kota (from desert people to sedentary people ). Berbeda dengan wilayah Islam lainnya, kelompok suku berber yang semula terpencar disatukan dalam sebuah gerakan keagamaan yang selanjutnya membentuk sebuah pemerintahan Islam, salah satunya adalah Dinasti Muwahhidun (Barat, al-Mohad). Pada mulanya Muwahhidun adalah gerakan dakwah yang dipimpin oleh Ibnu Tumart, namun kemudian berubah menjadi gerakan politik sampai berdirinya dinasti Muwahhidun oleh Abdul Mukmin. Kemajuan penting terletak pada gaya arsitektur yang khas. Dinasti ini akhirnya takluk ke tangan dinasti Marriniyyah yang merebut Marakesh tahun 1269 M